Ashy dermatosis with a positive patch test to gold sodium thiosulfate. Issue 2 (18th March 2019) - Korekawa, Ayumi; Nakajima, Koji; Nakano, Hajime; Sawamura, Daisuke
Abstract : Ashy dermatosis is a rare and idiopathic dermal melanosis. We present a case of ashy dermatosis with a positive patch test to gold sodium thiosulfate. After removing her dental implants containing gold, the development of additional lesions stopped.